Membrane perforation rate in lateral maxillary sinus floor augmentation using conventional rotating instruments and piezoelectric device—a meta-analysis - Corinne Jordi; Khaled Mukaddam; Jörg Thomas Lambrecht; Sebastian Kühl (International Journal of Implant Dentistry, 2018)
Abstract Objectives Maxillary sinus augmentation (MSA) is a successful and predictable intervention with low complication rates. Perforations of the Schneiderian membrane may occur impairing the general success. The aim of this study was to compare the incidence of membrane perforations between conventional rotating instruments and piezoelectric devices in a meta-analysis. Material and methods An electronic research on MEDLINE and PubMed database was performed evaluating the literature from 1980 till 2016. Meta-analysis was performed with the studies matching the inclusion criteria. The incidence of perforations between conventional and piezo during the lateral maxillary sinus floor elevation was determined, and forest plots and a t test for significance analysis were performed. Results The search provided 377 articles of which 69 could be included. Selected non-randomised and non-controlled prospective and retrospective studies were incorporated. Conventional rotary instruments were associated with a perforation rate of 24%, the piezoelectric devices with 8% with statistically significant difference between both modalities (p < 0.05). Conclusion Membrane perforations in MSA may be significantly reduced applying piezoelectrical devices for MSA.